The Corticosteroids Intralesional Injections as a Treatment of Oral Lichen Planus: Systematic Literature Review - I Nyoman Gede Juwita Putra (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction. Oral Lichen Planus (OLP) is a chronic immunological disorder that is inflammatory in form. Unlike skin lesions, oral lesions are more resistant to local and systemic therapy. The aim of this literature review is to explain alternative therapies in OLP cases using intralesional injection techniques. Literature Review. In general, OLP lesions in the oral cavity have no symptoms, but the atrophic-erosive form has mild symptoms such as discomfort and soreness. OLP therapy can generally be carried out with systemic or local therapy, however, OLP therapy is a long-term therapy that can be a challenge of the treatment, particularly in complex medical patients. Discussion. The use of corticosteroids in oral diseases is generally as anti-inflammatory, anti-proliferative, and immunosuppressive. Various methods, such as topical and systemic corticosteroids, griseofulvin, topical retinoids, hyaluronic acid, tetracycline, and topical cyclosporine, have been used to reduce morbidity. From several previous studies, Triamcinolone acetonide injection is a corticosteroid commonly used in OLP therapy in varying doses. In general, Triamcinolone acetonide injection is given in a dose of 20mg/ml or 40mg/ml. Conclusion. Injectable corticosteroids, especially Triamcinolone acetonide, are an effective therapy as an OLP treatment that can minimize the side effects of long-term corticosteroid therapy.